Changes in liver proteome expression of Senegalese sole (Solea senegalensis) in response to repeated handling stress - Cordeiro, O. (2014)
The Senegalese sole, a high-value flatfish, is a good candidate for aquaculture production. Nevertheless, there are still issues regarding this species’ sensitivity to stress in captivity. We aimed to characterize the hepatic proteome expression for this species in response to repeated handling and identify potential molecular markers that indicate a physiological response to chronic stress. Two groups of fish were reared in duplicate for 28 days, one of them weekly exposed to handling stress (including hypoxia) for 3 min, and the other left undisturbed. Two-dimensional electrophoresis enabled the detection of 287 spots significantly affected by repeated handling stress (Wilcoxon–Mann–Whitney U test, p<0.05), 33 of which could be reliably identified by peptide mass spectrometry. Chronic exposure to stress seems to have affected protein synthesis, folding and turnover (40S ribosomal protein S12, cathepsin B, disulfide-isomerase A3 precursor, cell-division cycle 48, and five distinct heat shock proteins), amino acid metabolism, urea cycle and methylation/folate pathways (methionine adenosyltransferase I α, phenylalanine hydroxylase, mitochondrial agmatinase, serine hydroxymethyltransferase, 3-hydroxyanthranilate 3,4-dioxygenase, and betaine homocysteine methyltransferase), cytoskeletal (40S ribosomal protein SA, α-actin, β-actin, α-tubulin, and cytokeratin K18), aldehyde detoxification (aldehyde dehydrogenase 4A1 family and aldehyde dehydrogenase 7A1 family), carbohydrate metabolism and energy homeostasis (fatty acid-binding protein, enolase 3, enolase 1, phosphoglycerate kinase, glyceraldehyde-3-phosphate dehydrogenase, aconitase 1, mitochondrial ATP synthase α-subunit, and electron-transfer flavoprotein α polypeptide), iron and selenium homeostasis (transferrin and selenium binding protein 1), steroid hormone metabolism (3-oxo-5-β-steroid 4-dehydrogenase), and purine salvage (hypoxanthine phosphoribosyltransferase). Further characterization is required to fully assess the potential of these markers for the monitoring of fish stress response to chronic stressors of aquaculture environment.